Multimodal MRI analysis of microstructural and functional connectivity brain changes following systematic audio-visual training in a virtual environment - Kholoud Alwashmi; Fiona Rowe; Georg Meyer (NeuroImage)
Recent work has shown rapid microstructural brain changes in response to learning new tasks. These cognitive tasks tend to draw on multiple brain regions connected by white matter (WM) tracts. Therefore, behavioural performance change is likely to be the result of microstructural, functional activation, and connectivity changes in extended neural networks.Here we show for the first time that learning-induced microstructural change in WM tracts, quantified with diffusion tensor and kurtosis imaging (DTI, DKI) is linked to functional connectivity changes in brain areas that use these tracts to communicate.Twenty healthy participants engaged in a month of virtual reality (VR) systematic audiovisual (AV) training. DTI analysis using repeated-measures ANOVA unveiled a decrease in mean diffusivity (MD) in the SLF II, alongside a significant increase in fractional anisotropy (FA) in optic radiations post-training, persisting in the follow-up (FU) assessment (post: MD t(76) = 6.13, p < 0.001, FA t(76) = 3.68, p < 0.01, FU: MD t(76) = 4.51, p < 0.001, FA t(76) = 2.989, p < 0.05). The MD reduction across participants was significantly correlated with the observed behavioural performance gains.A functional connectivity (FC) analysis showed significantly enhanced functional activity correlation between primary visual and auditory cortices post-training, which was evident by the DKI microstructural changes found within these two regions as well as in the sagittal stratum including WM tracts connecting occipital and temporal lobes (mean kurtosis (MK): cuneus t(19)=2.3 p < 0.05, transverse temporal t(19)=2.6 p < 0.05, radial kurtosis (RK): sagittal stratum t(19)=2.3 p < 0.05). DTI and DKI show complementary data, both of which are consistent with the task-relevant brain networks. The results demonstrate the utility of multimodal imaging analysis to provide complementary evidence for brain changes at the level of networks.In summary, our study shows the complex relationship between microstructural adaptations and functional connectivity, unveiling the potential of multisensory integration within immersive VR training. These findings have implications for learning and rehabilitation strategies, facilitating more effective interventions within virtual environments.